1998
DOI: 10.2105/ajph.88.9.1325
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of homelessness among adolescents in the United States.

Abstract: OBJECTIVES: Homeless adolescents represent one of the nation's most vulnerable populations. This study reports the 12-month prevalence of homeless episodes among US adolescents. METHODS: Personal, audiotaped interviews were conducted in 1992 and 1993 with a representative household sample of 6496 adolescents aged 12 to 17 as part of the Youth Risk behavior Survey sponsored by the Centers for Disease Control and Prevention. Respondents reported whether they had spent the night in any of a variety of locations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
124
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 196 publications
(125 citation statements)
references
References 11 publications
1
124
0
Order By: Relevance
“…1 Relative to housed youth, these youth are at increased risk for a myriad of health and behavioral health problems, including substance abuse, sexually transmitted diseases, poor mental health outcomes, violence, and victimization. [2][3][4][5] Recent work among homeless adults has suggested that cell phone technology may present unique opportunities for working with transient populations.…”
Section: Introductionmentioning
confidence: 99%
“…1 Relative to housed youth, these youth are at increased risk for a myriad of health and behavioral health problems, including substance abuse, sexually transmitted diseases, poor mental health outcomes, violence, and victimization. [2][3][4][5] Recent work among homeless adults has suggested that cell phone technology may present unique opportunities for working with transient populations.…”
Section: Introductionmentioning
confidence: 99%
“…Youth now make up to one-third of Canada's homeless population, with approximately 8,000 -11,000 youth homeless each night (Canada Mortgage and Housing Corporation, 2001). In the United States, the number of homeless youth ranges anywhere from 500,000 (National Coalition for the Homeless, 2006) up to 2 million (Ringwalt et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Representative cross-sectional data suggest that 1.7 million youth [2], approximately 7.6% of U.S. youth, experience at least one night of homelessness annually [3]. Globally, there is a perception that leaving home leads to chronic homelessness, but there are no longitudinal data to support or dispute this assumption.…”
Section: Introductionmentioning
confidence: 99%